A new, online culture war? The communication world of Breitbart.com. Issue 3 (3rd July 2019) - Davis, Mark
ABSTRACT: Public debate about the US culture wars reached a rancorous peak in the 1990s. At the same time, a no less contested scholarly debate was taking place over the significance of the culture wars, with many critics of the period dismissing the culture wars as an elite affair – a 'war of words' – that mattered little to ordinary Americans. Meanwhile, recent accounts of the culture wars have declared them 'over'. In this paper, I revisit the culture wars through the lens of far right website Breitbart.com, to show how Breitbart deploys a 'culture wars discourse' that reinvigorates the key ideas that animated the US culture wars of the 1980s and 1990s. The manifest political influence of sites such as Breitbart, I argue, represents a new development in the process by which cultural politics are increasingly framed by digital networked media.